(untitled) (Neo Scientific Peer Reviewed Journal, 2024)
In recent years, the advent of electronic books, commonly known as e-books, has revolutionized the way we access and consume information. With the rapid growth of the Information Technology (IT) industry, e-books have become a popular choice for learners seeking knowledge in this field. This article aims to explore the advantages and disadvantages of e-books for IT learners, analyzing their impact on learning outcomes, accessibility, convenience, interactivity, and the potential drawbacks associated with digital reading.